Chlorpromazine Electro‐oxidation at BDD Electrode Modified with nZVI Nanoparticles Impregnated NiAl LDH. Issue 6 (6th February 2020) - Djebbi, Mohamed Amine; Boubakri, Saber; Braiek, Mohamed; Jaffrezic‐Renault, Nicole; Namour, Philippe; Amara, Abdesslem Ben Haj
Abstract: Nanocomposite of nanoscale zero‐valent iron (nZVI) and layered double hydroxide (LDH) was used as modifier for boron‐doped diamond electrode in determination of anti‐psychotic drug chlorpromazine (CPZ). nZVI nanoparticles were prepared by liquid phase reduction of ferric chloride with sodium borohydride on the surface of NiAl LDH matrix owing to the strong exchange and confinement efficiency of LDH. The structure, binding and surface properties of the nZVI@LDH nanocomposite were monitored using powder X‐ray diffractometry, FT‐IR spectroscopy, scanning and transmission microscopy and BET techniques. The electrochemical properties of the modified electrode were investigated by CV and EIS, performed in a phosphate buffer containing ferro/ferricyanide as redox probe. The modified electrode exhibited excellent electrochemical performance compared with unmodified electrode. As regard potential application of the nanocomposite surface to the CPZ detection, square‐wave voltammetric signals showed a good linear correlation over CPZ concentrations in a broad range from 0.1 to 8.0 μM with low detection limit of 0.005 μM. Nevertheless, these results suggest that the proposed nanocomposite modifier surface provides exceptional synergy and significant enhancement effect to the voltammetric response of CPZ and thus could be applied as highly efficient and stable platform of sensors in clinical analysis. Abstract :